2016
DOI: 10.3390/molecules21070827
|View full text |Cite
|
Sign up to set email alerts
|

Dual Behavior of Iodine Species in Condensation of Anilines and Vinyl Ethers Affording 2-Methylquinolines

Abstract: Abstract:A metal-free, mild and efficient method for the synthesis of 2-methylquinolines was successfully developed by condensation of anilines with vinyl ethers in the presence of catalytic amount of iodine. Modification of both pyridine and benzene moieties was easily achieved by changing only the vinyl ether and aniline. In this reaction, the iodine species was revealed to show dual behavior; molecular iodine serves as an oxidant, while its reduced form, hydrogen iodide, activates the vinyl ether. The redox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Based on the above results and on previous reports, [26][27][28] a possible mechanism has been proposed with model substrates 6a and 7a (Scheme 4). Iodine plays its first role as a Lewis acid by activating the carbonyl function of 7a to facilitate the nucleophilic attack of amine 6a and generate the respective imine 9a.…”
Section: Accepted Manuscriptsupporting
confidence: 55%
“…Based on the above results and on previous reports, [26][27][28] a possible mechanism has been proposed with model substrates 6a and 7a (Scheme 4). Iodine plays its first role as a Lewis acid by activating the carbonyl function of 7a to facilitate the nucleophilic attack of amine 6a and generate the respective imine 9a.…”
Section: Accepted Manuscriptsupporting
confidence: 55%
“…3-Benzyloxyacetanilide 14 efficiently underwent Vilsmeier–Haack cyclization [ 20 ] to afford 2-chloro-3-formyl quinoline derivative 15 and subsequent hydrodechlorination of 15 was realized to yield 16 using Pd(PPh 3 ) 4 /Et 3 N/HCO 2 H system in DMF at 110 °C. Next, a metal-free, mild and efficient method was employed for the synthesis of 2-methylquinoline moiety 18 by condensation of 4-(benzyloxy)aniline 17 with ethyl vinyl ether in the presence of catalytic amount of iodine [ 21 ]. To achieve isoquinoline moiety 23 , Heck reaction was performed on 5-(benzyloxy)-2-bromobenzaldehyde 20 which in turn obtained from 2-bromo-5-hydroxybenzaldehyde 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an iodine-mediated reaction was applied to the synthesis of these quinolines. Nishiwaki and co-workers developed a mild and inexpensive method for the synthesis of 2methylquinolines by condensation of anilines with vinyl ethers in the presence of catalytic amount of iodine (5 mol%) in benzene at 80 C for 2 h. 56 Interestingly, employing p-TsOH this reaction instead of iodine, it was demonstrated that p-toluenesulfonic acid did not catalyse this reaction at 80 C and it was necessary to heat at 120 C. In this reaction, the iodine species was revealed to show dual behaviour; molecular iodine serves as an oxidant, while its reduced form, hydrogen iodide, activates the vinyl ether. followed by DDQ-promoted dehydrogenative aromatization (Scheme 5, route B).…”
Section: Synthesis and Chemistry Of Quinolines For Antiparasitic Quinmentioning
confidence: 99%